2022
DOI: 10.1017/s0022215122000536
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of otorhinolaryngological manifestations of coronavirus disease 2019 in paediatric patients

Abstract: Background This meta-analysis provides a quantitative measure of the otorhinolaryngological manifestations of coronavirus disease 2019 in children. Methods A structured literature review was carried out using PubMed, Embase and Cochrane Central, employing pertinent search terms. The statistical analysis was performed using Stata version 14.2 software, and the analysed data were expressed as the pooled prevalence of the symptoms with 95 per cent confidence intervals. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…Hijazi et al found that the only otologic symptoms in 660 pediatric patients with COVID-19 were otalgia and ear fullness, reported in 1.8 % and 0.5 % of cases, respectively [16] . A recent systematic review and meta-analysis of otorhinolaryngological manifestations of COVID-19 in pediatric patients confirmed that hearing loss and vertigo were rarely reported [17] . A study by Tufatulin et al that evaluated 87 children in three cities in Russia found no cases of hearing loss or central auditory processing disorders after SARS-CoV-2 infection [18] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hijazi et al found that the only otologic symptoms in 660 pediatric patients with COVID-19 were otalgia and ear fullness, reported in 1.8 % and 0.5 % of cases, respectively [16] . A recent systematic review and meta-analysis of otorhinolaryngological manifestations of COVID-19 in pediatric patients confirmed that hearing loss and vertigo were rarely reported [17] . A study by Tufatulin et al that evaluated 87 children in three cities in Russia found no cases of hearing loss or central auditory processing disorders after SARS-CoV-2 infection [18] .…”
Section: Discussionmentioning
confidence: 95%
“…The present study assessed the prevalence of audiological and vestibular symptoms following SARS-COV-2 infection or COVID-19 vaccination among children aged 5–11 years who attended a third-level referral audiological center. While several studies have described audio-vestibular disorders, such as sudden sensorineural hearing loss, tinnitus, and vertigo, as possible manifestations following SARS-CoV-2 infection [11] , [12] and COVID-19 vaccines in adults [13] , [14] , [15] , there are very few reports concerning the pediatric population [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the omicron-caused prevalence of hyposmia for the different major ethnicities, and the total population size of these major ethnicities (obtained from the WHO website: https://www.worldometers.info/geography/7-continents/), and using the estimated numbers of COVID cases from the Institute for Health Metrics and Evaluation [6], we can estimate the number of adults in different ethnic populations that can be expected to experience olfactory dysfunction due to omicron infection (Table 3). Since children make up approximately 25% of the world population, we subtracted 25% from each of the population sizes to account for children – which are not included in our review, because there are too few studies reporting on olfactory dysfunction in omicron-infected children, and children with COVID are known to have much less olfactory dysfunction than adults [25]. Assuming a COVID infection of 90% among populations [6], we predict for people of European ancestry a total number of 71.1 million adults with hyposmia out of 0.6 billion (11.7% prevalence), 23.2 million adults with hyposmia out of 0.5 billion Latinos/Hispanics (4.9% prevalence), 29.3 million adults with hyposmia out of 0.9 billion Africans (3.1% prevalence), 32.1 million adults with hyposmia out of 1.7 billion East Asians (1.9% prevalence), 37.8 million adults with hyposmia out of 1.3 billion South Asians (2.8% prevalence), and 7.4 million adults with hyposmia out of 0.3 billion in the Middle East (2.2% prevalence), adding to a total of 200.9 million adult people with olfactory dysfunction, as summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in the enzyme may account for inter-individual variability in olfactory perception [16]. Furthermore, UDP glycosyltransferases are expressed differentially with aging [110] which could explain the increased olfactory dysfunction seen in young adults (but less in children or older people [25,99]), and expression of UDP glycosyltransferase also differs between genders [111], which may explain the higher female susceptibility to olfactory dysfunction [99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation